2010
DOI: 10.1177/0276146710380224
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Justice Model for Marketing to the Poor: An Extension of S-D Logic to Distributive Justice and Macromarketing

Abstract: As multinational corporations (MNCs) increasingly turn their attention to the fast growing markets of China, India, Brazil, and other developing areas, the question of fair treatment of consumers and other residents of those areas is more intensively debated than ever before. In essence, issues of "distributive justice" come to the fore, that is, are the benefits and burdens of rapid economic development being fairly allocated among the parties and stakeholders to the expanded economic transactions? In respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…In order to develop this capability, firms are required to assume responsibility for action taken by their managers under the lens that reflects on building financial strength while respecting humanity and nurturing nature (Laczniak & Santos, 2011). This requirement of sustainability encourages managers to create and capture opportunities that allow them to achieve the objectives that can be related to the triple bottom line theory, i.e., making profit for stakeholders, considering the well-being of people connected to the business and caring for the planet by conserving or making optimum use of natural resources for performing business (Jamali, 2008).…”
Section: Operations Opportunitiesmentioning
confidence: 99%
“…In order to develop this capability, firms are required to assume responsibility for action taken by their managers under the lens that reflects on building financial strength while respecting humanity and nurturing nature (Laczniak & Santos, 2011). This requirement of sustainability encourages managers to create and capture opportunities that allow them to achieve the objectives that can be related to the triple bottom line theory, i.e., making profit for stakeholders, considering the well-being of people connected to the business and caring for the planet by conserving or making optimum use of natural resources for performing business (Jamali, 2008).…”
Section: Operations Opportunitiesmentioning
confidence: 99%
“…Though SDL has its critics (for example Campbell et al [2013]), it has encouraged many academics to leave the constraints of the traditional marketing domain and contribute to the emerging paradigm [Li, Petrick, 2007;Warnaby, 2009;Löbler, 2011;Brodie et al, 2011;Laczniak, Santos, 2011;Karpen et al, 2012;Edvardson, Tronvoll, 2013;. This lively academic interest suggests the importance of further research in this area.…”
Section: Value In Service Dominant Logicmentioning
confidence: 99%
“…Scholars from international relations, global public policy, law and political studies have shown that the emerging water crisis will bring latent transnational conflicts amongst nations which claim authority over the same river, lake, basin, Either from a transboundary, national or regional angle water 'wars' and disputes stem from opposing and conflicting interests between individual, household, agricultural and industrial water users whose intentions, beliefs and actions have been structured and oscillated, since the 1980s, by those who promote water privatization and others supporting public sector water management solutions. The efficiency and cooperation of global, national or regional water markets heavily depends on institutional frameworks and public policies which embrace, protect and cultivate an ethos of fair distribution of water resources through ethical and sustainable marketing systems (Ferrell and Ferrell 2008;Laczniak and Santos 2011).…”
Section: The Political Dimension Of Water Marketingmentioning
confidence: 99%